Soucasné moznosti prenatální diagnostiky kongenitálni diafragmatické hernie - Stranák, Z; Kucerová, I; Urbánková, I; Goldová, B; Vítková, I; Rygl, M; Pýcha, K; Krofta, L (Ceska gynekologie, 2009)
OBJECTIVE: The aim of this article is to review the current options of prenatal diagnosis in congential diaphragmatic hernia (CDH). SUBJECT: Systematic review. SETTING: Institute for the Care of Mother and Child, 3rd Medical Faculty, Prague. SUBJECT AND METHOD: Review of recent published data. CONCLUSION: The basic method for prenatal diagnosis of congenital diaphragmatic hernia is 2D ultrasonography: measurement of lung-to-head ratio (LHR), observed to expected lung to head ratio (observed to expected LHR - O/E LHR), localization of diaphragmatic defect, assessment of liver position and presence of associated anomalies (negative prognostic factors). Prenatal diagnosis can be supplied with 3D ultrasonography and magnetic resonace (imaging methods for valid measurement of fetal lung volume and/or presence of associated congenital defects confirmation). The reactivity of intrapulmonary arteries are evaluated by hyperoxygenation test and measurement of arterial Doppler parameters. Isolated diaphragmatic hernia is not an indication for invasive prenatal diagnostic methods. Important part of succesful prenatal diagnosis and therapy of CDH is concentration of cases in specialized centre.
Keywords: magnetická rezonanční angiografie; Infant, Newborn; Pregnancy; lidé; Ultrasonography, Prenatal; ultrasonografie prenatální; Hernia, Diaphragmatic; vrozená brániční kýla; ženské pohlaví; Hernias, Diaphragmatic, Congenital; Humans; Magnetic Resonance Angiography; brániční hernie; Female; těhotenství; novorozenec